Exploring the Perceptions of Core Values of Nursing in Taiwanese Nursing Students at the Baccalaureate Level. Issue 2 (June 2016) - Lin, Chun-Chih; Han, Chin-Yen; Pan, I-Ju; Lin, Pi-Li
ABSTRACT: Background: The core values of nursing are a standard component of the nursing curriculum in Taiwan. Therefore, these values provide an essential guide for educating and evaluating the learning outcomes of nursing students. Student perceptions of those core values that relate to the process of curricula learning are key to measuring the core values of nursing. Purpose: This study explores the views on the core values of nursing of baccalaureate-level nursing students at a Taiwanese university. Methods: This qualitative study collected data from the reflection reports of 109 students and analyzed these data using thematic content analysis. Results: The results of this study identified that the learning of core values of nursing tends to utilize the latent curriculum rather than the open curriculum. Critical thinking was perceived and experienced by asking "why." General clinical skills and basic biomedical science were categorized collectively as care ability, which relates to the thinking, analysis, and mapping of client health problems. The value of communication and teamwork capability was defined as the sequential process of accepting, interacting, communicating, and collaborating. Caring was defined as contributing empathy with respect to one's self and to others. Ethics was defined as a moral perspective, as respecting others, and as prioritizing the needs of clients. Accountability was defined as a way of observing standards within the role given in a position. Finally, lifelong learning is a process of learning that encourages more aggressive learning. Conclusions/Implications for Practice: The progress of core values of nursing in this study reflects positive movement and achievement. The participants expressed the perception that the core values of nursing enhance understanding, which enables nursing educators to reframe the nursing curriculum to meet their learning needs. The perceptions of nursing students of core values of nursing may be used as a guide to increase clinical nursing competence in healthcare.